The European health report, 2005 : public health action for healthier children and population. (WHO regional publications. European series, 2005)
A synthesis of evidence and analyses from WHO and other sources, the report identifies both noncommunicable diseases as the main cause of the burden of disease on the European Region, and communicable diseases as an additional burden on eastern countries, caused by poverty and underfunded health services. It shows that using well-known, comprehensive interventions to tackle the seven leading risk factors - tobacco, alcohol, high blood pressure, high cholesterol, overweight, low fruit and vegetable intake, and physical inactivity - would largely prevent the seven leading conditions - ischaemic heart disease, unipolar depressive disorders, cerebrovascular disease, alcohol-use disorders, chronic pulmonary disease, lung cancer and road traffic injury. This creates a compelling argument for action.